Estratégias Transmídia para Plataformas Mobile: Estudo de caso Play Fanta - Souza, Eduardo Faustino de (2017)
The introduction of the transmedia into advertising has brought diverse options for exploring narrative universes. The games are part of this narrative range and are being increasingly introduced in campaigns, focusing on the loyalty and spontaneous propagation of brand in users. The Saving The Source campaign developed by the Coca-Cola Company in partnership with Ogilvy and Psyop focused on the use of this new market. Creating a worldwide mobile transmigration strategy reaching more than 168 million children, in 190 countries around the world. The methodology used is a case study with a qualitative view with bibliographical research, Internet documentary research, including the content and data of engagement from the campaign, besides qualitative interviews with professionals who worked in the campaign and specialists. The main conclusion is that the use of transmedia techniques, coupled with leading edge technologies have resulted in a strong branding impact.